Naticid gastropods from the middle Miocene of western Ukraine - Pedriali, Luca; Sosso, Maurizio; Dell’angelo, Bruno (Zootaxa, 2019)
The paper covers 11 species of naticid gastropods occurring in the lower Serravallian (Upper Badenian) strata of western Ukraine (Central Paratethys). The studied material (over 1,700 naticids) represents six genera and 11 species, of which eight are new: Cochlis odovychenorum, Cochlis ukrainensis, Tectonatica anistratenkorum, Tectonatica pseudoprietoi, Euspira sirenkoi, Payraudeautia ermesi, Payraudeautia sabrinae and Payraudeautia varovtsiana. Additionally, we have also identified Euspira protracta (Eichwald, 1830), Polinices staszici (Friedberg, 1923) and Sinum affinis (Eichwald, 1830). A lectotype of Sinum affinis is designated (ZISP 1/62208). Detailed descriptions of the protoconch and teleoconch morphology of the taxa involved, including SEM images, are presented.